Gender, ethnicity, and social change on the upper slave coast a history of the Anlo-Ewe - Greene, Sandra E. 1952- (Social history of Africa, 1996)
Sandra Greene argues convincingly that gender and ethnicity in precolonial Africa can only be understood together. Her book focuses on the history of the Anlo-Ewe of southeastern Ghana over three centuries and demonstrates that the very factors that affected social constructions of gender also had profound implications for the construction of ethnic identities. Greene documents the changes that occurred in ethnic boundaries as the community absorbed refugees, traders, and conquerors and later began to redefine the boundaries between insiders and outsiders. She then analyzes the way shifting ethnic definitions and competition for scarce resources affected gender relations. Clan elders increasingly sacrificed the interests of the young women under their authority in marital arrangements because of an increasing preference for clan endogamy. Greene explores the way some of these women were able to reassert their voices through membership in influential "outsider" religious orders. These new alignments formed a base of support from which Anlo women and a number of ethnic outsiders successfully challenged their own marginalization. Thus by the end of the nineteenth century, the boundary that separated insiders and outsiders in Anlo society and the ways in which men and women interacted had changed significantly. Greene eschews simplistic analyses of oppression and agency. All in Anlo society are given a voice and allowed to speak from their own perspective, establishing a new and exciting standard for analyzing the history of social relations in precolonial Africa.